2021
DOI: 10.1177/2325967121s00067
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Adolescent Hip Arthroscopy From the PHIS Database: 2008 to 2018

Abstract: Background: Previous studies have suggested that hip arthroscopy has been performed with increasing frequency. Few studies have examined this trend in the adolescent population. Purpose: The purpose of this study was to evaluate the trend in the frequency of hip arthroscopy in adolescents standardized by total orthopaedic surgeries in adolescents at pediatric hospitals in the United States. Methods: The Pediatric Health Information System (PHIS) database was queried for patients aged 10 to 19 years who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…However, our conclusions should be interpreted in light of several limitations. Although the PHIS database has been utilized in many pediatric orthopaedic studies, [31][32][33] there are some inherent limitations to a multicenter database of this nature. One major limitation seen when using the PHIS database is related to the coding nuances/accuracy, the accuracy of the diagnosis was not able to be confirmed and the laterality is not always accounted for.…”
Section: Discussionmentioning
confidence: 99%
“…However, our conclusions should be interpreted in light of several limitations. Although the PHIS database has been utilized in many pediatric orthopaedic studies, [31][32][33] there are some inherent limitations to a multicenter database of this nature. One major limitation seen when using the PHIS database is related to the coding nuances/accuracy, the accuracy of the diagnosis was not able to be confirmed and the laterality is not always accounted for.…”
Section: Discussionmentioning
confidence: 99%
“…Hassan et al queried the Pediatric Health Information System (PHIS) Database for patients who underwent hip arthroscopy and were between 10 and 19 years of age and found that, over 10 years, the number of hip arthroscopies had a 3.9-fold increase compared with the number of total orthopaedic surgical procedures in adolescents. The authors postulated that this increase may be due to improved understanding of hip pathology and increasing sports participation 59 . Hanke et al found that 52% of hockey players enrolled in a longitudinal MRI study at the ages of 12 and 13 years developed cam morphology within 3 years.…”
Section: Hip Preservationmentioning
confidence: 99%
“…However, variations in reporting still exist among participating institutions as the way they report CPT and ICD-9/10 codes for particular procedures or diagnoses may vary. The PHIS database gathers data from large tertiary care referral pediatric hospitals, so the patient population it represents may not be generalizable to the community or nonspecialty hospitals 13,23…”
mentioning
confidence: 99%
“…The PHIS database gathers data from large tertiary care referral pediatric hospitals, so the patient population it represents may not be generalizable to the community or nonspecialty hospitals. 13,23 Each database has its strengths and weaknesses, and by exploring their differences, we may be able to identify which databases are more suitable in answering certain research questions. To our knowledge, there are no studies assessing differences in patients, data, and outcomes between these 3 commonly used databases.…”
mentioning
confidence: 99%